State of charge estimation for lithium-ion battery based on random forests technique with gravitational search algorithm - Lipu M.S.H.; Ayob A.; Saad M.H.M.; Hussain A.; Hannan M.A.; Faisal M. (IEEE Computer Society, 2023)
Charging (batteries); Decision trees; Electric vehicles; Forestry; Ions; Learning algorithms; Lithium-ion batteries; Radial basis function networks; Gravitational search algorithm (GSA); Gravitational search algorithms; Radial basis function neural networks; Random forests; State of charge; State of charge estimations (SOC); State-of-charge estimation; Sustainable transportation systems; Battery management systems